Gastrocolic Fistula: A Rare Presentation of Colon Cancer - Chukwunonso Chime; Madhavi Ravi; Myrta Daniel; Harish Patel; Bhavna Balar (Case Reports in Gastrointestinal Medicine)
Gastrocolic fistulae have been described for benign conditions including penetrating peptic ulcer and complicated pancreatitis. Malignant etiology can arise from gastric or colon cancer and is a rare and late complication with an incidence of 0.3-0.4%. Usual presentation is the classic triad of weight loss, diarrhea, and feculent vomiting. Barium enema has been shown to have the highest diagnostic accuracy but endoscopy offers additional advantage of biopsy to aid in diagnosis of malignant etiology; the role of computed tomography (CT) scan is controversial. Treatment by one-stage en bloc surgical approach is the current acceptable standard of care with variable recurrence and survival rates. Adjuvant chemotherapy would be based on lymph node involvement and patient discussion.